The role of Primary Energy Factors (PEF) for electricity in the evaluation and comparison of building energy performance: An investigation on European nZEBs according to EN 17423:2020. (December 2022) - Bilardo, Matteo; Galatà, Sara; Fabrizio, Enrico
Highlights: Primary energy factors (PEF) for electricity are temporally and geographically variable. The EN 17423: 2020 standard proposes a unified method for calculating PEFs. Building performance is significantly affected by the impact of PEFs. The adoption of shared PEF allows an adequate comparison between buildings. PEF assessment can support national energy policies in the energy transition. Abstract: Evaluating the energy performance of buildings is a fundamental aspect for quantifying the impact of national energy policies supporting energy transition and sustainable development of countries. However, evaluations carried out on final energy consumption risk leading to approximate solutions that do not take into account the generation, transmission and distribution efficiency of energy systems. Furthermore, it is increasingly difficult to compare similar buildings that belong to different geographical contexts. To overcome these problems, a common solution, that is adopted at European and international level, is the use of the concept of primary energy, and the relative primary energy factor (PEF). The current assessment of primary energy for the performance of European buildings is governed by individual national laws, which are often out-to-date and not representative of current national energy systems. In this work, the recent EN 17423:2020 standard was adopted to apply a harmonized methodology in the evaluation of PEF for different European countries, considering the electricity energy vector. The results demonstrated first an important variation in the primary energy factor over the last 20 years, with decreases from -7% (in France) to -32% (in Denmark). Using this methodology, the primary energy needs of 37 European representatives nearly Zero Energy Buildings (nZEBs), located in 11 different member countries, were assessed. For the first time in literature, it was possible to compare European buildings energy performance following a standardized assessment procedure. The implications of this work represent a starting point for comparisons on the European building stock, also indicating the need for an update of national regulations regarding the assessments of the energy performance of buildings.